2012
DOI: 10.1111/j.1600-0463.2012.02936.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and levels of alpha‐1‐antitrypsin in the lung and plasma in smokers and chronic obstructive pulmonary disease

Abstract: Our recent non‐biased proteomic screening study revealed elevated SerpinA1 i.e. alpha‐1‐antitrypsin (AAT) levels in induced sputum of smokers with Chronic obstructive pulmonary disease (COPD). This study was designed to further investigate the role of AAT in smokers and subjects with COPD. The expression/distribution of AAT was studied by immunohistochemistry/digital image morphometry in the lung, by Western blot in the lung and sputum, and by ELISA in the plasma at baseline (n = 349) and after a 2‐year follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 47 publications
1
8
0
1
Order By: Relevance
“…Serapinas et al [ 20 ] demonstrated that the increase in the AAT concentration in blood serum is related to smoking, as they observed a higher concentration of this enzyme in current smokers and exsmokers than in never-smokers. Higher level of AAT in the blood serum of smokers was also demonstrated by Linja-Aho et al [ 10 ]. The concentration of AAT was higher in smokers without COPD and in smokers with COPD than in healthy nonsmokers.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Serapinas et al [ 20 ] demonstrated that the increase in the AAT concentration in blood serum is related to smoking, as they observed a higher concentration of this enzyme in current smokers and exsmokers than in never-smokers. Higher level of AAT in the blood serum of smokers was also demonstrated by Linja-Aho et al [ 10 ]. The concentration of AAT was higher in smokers without COPD and in smokers with COPD than in healthy nonsmokers.…”
Section: Discussionsupporting
confidence: 63%
“…AAT is a protein belonging to serine protease inhibitors. It is synthesized mainly in the liver and belongs to the acute phase plasma proteins associated with acute inflammatory episodes including infectious and obstructive lung diseases [ 10 ]. It is hypothesized that plasma AAT may be a noninvasive marker of smoking-related inflammation or COPD [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is due to the differences in risk factors for pregnancy: SERPINA1 was increased in placentas of obese mothers [26] and decreased in preeclamptic mothers [27]. SERPINA1 is increased in the lung and sputum of smokers [28], which, together with our data and known effects of smoking on the placenta [29], suggests that specific SERPINA1 isoforms could serve as a biomarker for oxidative stress. It is also possible that the alterations in placental SERPINA1 expression levels reflect responses to external stress factors and, therefore, could reflect the overall maturation process or well-being of the foeto-placental unit.…”
Section: Discussionmentioning
confidence: 49%
“…Deficiency of α-1-antitrypsin, encoded by Serpina1s, renders the organism vulnerable to breakdown by neutrophil elastases and the deficiency has been correlated to chronic obstructive pulmonary disease (COPD) (Chappell et al, 2006;Dahl et al, 2002;Kueppers et al, 1969). In addition, studies have shown a correlation between cigarette smoking and increased levels of α-1-antitrypsin in the lungs (Linja-Aho et al, 2013;Olsen et al, 1975). The observed differential expression of Serpina1s in the present study may indicate that CNT Large exposure could be a risk factor for COPD in a similar fashion to cigarette smoke.…”
Section: Discussionmentioning
confidence: 98%